10D massive type IIA supergravities as the uplift of parabolic M2‐brane torus bundles. Issue 4 (23rd December 2015) - Garcia del Moral, Maria Pilar; Restuccia, Alvaro
Abstract : We remark that the two 10D massive deformations of the N = 2 maximal type IIA supergravity (Romans and HLW supergravity) are associated to the low energy limit of the uplift to 10D of M2‐brane torus bundles with parabolic monodromy linearly and non‐linearly realized respectively. Romans supergravity corresponds to M2‐brane compactified on a twice‐punctured torus bundle.